Hydrothermal carbon one-step conversion device and process
Patent Information
- Application Number
- CN202610523210.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]现有水热炭化技术主要存在以下不足:无法在单一工艺过程中同时实现水热炭的碳化、高附加值纳米碳材料的原位生成以及水热炭表面官能团的定向保留与调控
(1)本发明提供的水热炭一步法转化工艺,通过将原料配浆、程序升温反应(控制pH为4-6以原位生成粒径≤10nm的碳量子点)和程序降温恒温处理(以5-15℃/min的速率降温至100-150℃并恒温0.5-2小时)集成于同一反应器中,实现了水热炭化、碳量子点原位负载和表面官能团定向保留的一体化;与现有技术相比,本工艺无需后续的物理/化学活化或金属浸渍改性步骤,通过程序降温有效抑制了活性官能团的热分解,使得水热炭表面的羧基、羟基等含氧官能团保留率显著提高,同时一步制得了负载碳量子点的功能化水热炭复合材料,显著简化了工艺流程、降低了能耗,并实现了水热炭表面化学性质的精准可控制备。
Smart Images

Figure CN122917810A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrothermal carbon technology, and in particular to a one-step hydrothermal carbon conversion device and process. Background Technology
[0002] Hydrothermal carbonization (HCT) is a thermochemical technology that converts biomass into hydrothermal carbon in a closed reactor using water as the reaction medium at relatively low temperatures (180-300℃) and autogenous pressure. Compared to pyrolysis, HTC eliminates the need for pre-drying of the raw materials, making it particularly suitable for treating biomass with high moisture content, such as medicinal herb residues, sludge, algae, and black liquor from papermaking.
[0003] Existing hydrothermal carbonization technologies have the following main shortcomings: they cannot simultaneously achieve the carbonization of hydrothermal carbon, the in-situ generation of high-value-added nano-carbon materials, and the directional retention and regulation of functional groups on the surface of hydrothermal carbon in a single process. Specifically, traditional hydrothermal carbonization only completes the basic conversion of biomass into hydrothermal carbon, resulting in products with limited functionality and uncontrollable surface chemical properties. Summary of the Invention
[0004] The present invention aims to provide a hydrothermal carbon one-step conversion device and process to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A one-step hydrothermal carbon conversion process includes the following steps: S1: Crush solid biomass raw materials to 40-200 mesh, mix with water at a solid-liquid ratio of 1:5-1:20; or use liquid biomass raw materials directly; optionally add 0-5% of the raw material mass of surfactant and / or 0-5% of metal salt modifier, stir evenly to form a slurry; S2: Pump the slurry into a closed reactor and heat it to 180-300°C at a heating rate of 2-10°C / min. Maintain the temperature under autogenous pressure for 1-6 hours. Control the pH of the system to 4-6 during the reaction. S3: After the heat preservation is completed, cool down to 100-150℃ at a rate of 5-15℃ / min and keep at a constant temperature for 0.5-2 hours; S4: After the reaction is complete, the material is discharged, and after solid-liquid separation, washing and drying, a hydrothermal carbon composite material loaded with carbon quantum dots is obtained.
[0006] Preferably, the metal salt modifier is selected from Fe(NO3)3·9H2O or FeCl3·6H2O, and the amount added is 1-5% of the raw material mass.
[0007] Preferably, the surfactant is selected from Span 80, Tween 80 or sodium lignosulfonate; wherein the amount of Span 80 added is 2-5%, the amount of Tween 80 added is 1-3%, and the amount of sodium lignosulfonate added is 3-5%.
[0008] Preferably, the surfactant has an HLB value of ≤10 or ≥14.
[0009] Preferably, the method for controlling the pH value of the system to 4-6 in step two is as follows: add 0.5-3% organic acid by weight of the raw material to the raw material slurry, wherein the organic acid is selected from acetic acid, citric acid or lignin sulfonic acid; or use formic acid, acetic acid or propionic acid generated during the hydrothermal carbonization of biomass as pH adjusters.
[0010] Preferably, different combinations of process parameters are selected according to the application scenario of the target product: When used for the remediation of heavy metal pollution: reaction temperature 180-220℃, holding time 4-6 hours, surfactant 3-5% sodium lignosulfonate, no metal salt modifier added or only Ca added. 2+ Salt; When used to promote anaerobic fermentation: reaction temperature 220-260℃, holding time 2-4 hours, metal salt modifier Fe(NO3)3·9H2O 2-4%, surfactant Span 80 2-3%; When used for solid fuels: reaction temperature 260-300℃, holding time 4-6 hours, solid-liquid ratio 1:10~1:15, no surfactant added, add 1-3% K2CO3 or KHCO3.
[0011] Preferably, when the biomass raw material is papermaking black liquor, the pH of the black liquor is adjusted to 4-6 with acid; the reaction temperature is controlled at 220-280℃, the holding time is 4-8 hours, and a metal salt modifier is optionally added.
[0012] Preferably, the process is a continuous process: the raw material slurry is continuously fed into the reactor at a constant flow rate by a high-pressure slurry pump, while the reacted material is continuously discharged through a back pressure valve; after online solid-liquid separation, the liquid phase is concentrated and reused in step one.
[0013] A hydrothermal carbon one-step conversion device is also proposed, comprising: The high-temperature, high-pressure, and corrosion-resistant reactor integrates a multi-stage mixer, heat exchange coils, and a porous material distributor. Multiple temperature sensors, pressure sensors, and online pH sensors are installed inside the reactor, as well as an external heating / cooling circulation system connected to the heat exchange coil. All sensors and the heating / cooling circulation system are connected to a PLC controller. High-pressure slurry pump and high-pressure metering injection pump are connected to the material inlet of the reactor; Back pressure valve installed on the material outlet pipeline of the reactor; An online solid-liquid separator, a washing device, and a drying device are connected sequentially after the material outlet of the reactor; The liquid phase outlet of the online solid-liquid separator is connected to the inlet of the high-pressure slurry pump via a concentration device.
[0014] The beneficial effects of this technical solution compared to existing technologies are as follows: (1) The hydrothermal carbon one-step conversion process provided by the present invention integrates raw material preparation, programmed temperature rise reaction (controlling pH to 4-6 to generate carbon quantum dots with a particle size ≤10nm in situ) and programmed cooling isothermal treatment (cooling to 100-150℃ at a rate of 5-15℃ / min and holding at 0.5-2 hours) in the same reactor, realizing the integration of hydrothermal carbonization, in-situ loading of carbon quantum dots and directional retention of surface functional groups. Compared with the prior art, this process does not require subsequent physical / chemical activation or metal impregnation modification steps. The programmed cooling effectively inhibits the thermal decomposition of active functional groups, which significantly improves the retention rate of oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface of hydrothermal carbon. At the same time, a functionalized hydrothermal carbon composite material loaded with carbon quantum dots is obtained in one step, which significantly simplifies the process flow, reduces energy consumption, and realizes the precise and controllable preparation of the chemical properties of the hydrothermal carbon surface. Attached Figure Description
[0015] Figure 1 Flowchart provided for this invention; Figure 2 The cumulative hydrogen production at different time points provided by this invention; Figure 3 The graph showing the changes in SMP concentration and glucose concentration at different time points provided by this invention; Figure label: Detailed Implementation The present invention will now be described in further detail with reference to the accompanying drawings and embodiments: Example 1 (Acidic hydrothermal carbon for heavy metal pollution remediation) 1. Raw material pretreatment Reed stalks were selected as raw material, sourced from an artificial wetland in Zibo, Shandong Province, and harvested after maturity in the previous growing season. The reed stalks were naturally air-dried and then cut into 1-2cm sections. They were washed three times repeatedly with purified water to remove surface ash, dirt, and other impurities. After washing, they were dried in an 85℃ oven until constant weight (drying time approximately 24 hours). The powder was then pulverized using a high-speed universal pulverizer and sieved through a standard 40-mesh sieve using a standard inspection sieve separator. The sieved reed stalk powder was then bagged and placed in a desiccator for later use.
[0016] The elemental composition of the reed straw raw material was determined to be: C 39.47%, H 6.02%, O 41.95%, N 1.17%, ash content 2.16%, and calorific value 15.83 MJ / kg. The raw material is weakly acidic, with a pH value of approximately 5.8.
[0017] 2. Pulp preparation and additive premixing Weigh 10g of the above-mentioned reed straw powder (dry basis), add 150mL of deionized water at a solid-liquid ratio of 1:15, and add 3wt.% (0.3g) of sodium lignosulfonate (SLS, HLB≈8.9) by weight of the raw material. Stir until a slurry is formed. Sodium lignosulfonate is an anionic surfactant, and its addition can significantly reduce the toxic equivalent of polycyclic aromatic hydrocarbons in hydrothermal char. No metal salt modifier is added in this embodiment.
[0018] Stir the slurry thoroughly for 15 minutes to ensure that the sodium lignosulfonate is evenly dispersed in the slurry. The slurry is brownish-red and has a pH of approximately 6.5.
[0019] 3. Temperature-programmed reaction The slurry was poured into a sealed reactor. The reactor was a specially designed reactor (made of Hastelloy C-276) that was resistant to high temperature, high pressure, and corrosion, and it integrated a static mixer, heat exchange coils, and a porous material distributor. After sealing the reactor, the heating program was set via a PLC controller: heating to 200°C at a heating rate of 5°C / min, and holding the reaction at that temperature under autogenous pressure for 6 hours.
[0020] During the reaction, the pH of the system is adjusted using organic acids such as formic acid, acetic acid, and propionic acid generated during the hydrothermal carbonization of reed straw. As the temperature increases, hemicellulose and cellulose hydrolyze to produce small-molecule organic acids, and the pH of the system gradually decreases from the initial 6.5 to around 5.5, without the need for external acid regulators. The self-generated pressure inside the reactor increases with increasing temperature, reaching approximately 1.5-1.8 MPa at 200℃.
[0021] 4. Programmed cooling and isothermal treatment After a 6-hour incubation period, cooling water was rapidly introduced through the heat exchange coil at a cooling rate of 10°C / min to rapidly cool the temperature to 120°C, where it was then held at that temperature for 1 hour. The purpose of programmed cooling is to "lock in" the acidic functional groups (such as carboxyl and hydroxyl groups) formed in the low-temperature range, preventing excessive decomposition of these functional groups due to prolonged high temperatures during natural cooling. Studies have shown that relatively low temperatures (180-220°C) favor the formation of more acidic oxygen-containing functional groups, while these functional groups partially decompose at higher temperatures. Programmed cooling can directionally preserve acidic functional groups such as carboxyl and hydroxyl groups.
[0022] 5. Discharge and Separation After the reaction is complete, the reactor is opened and the material is discharged. A Buchner funnel with a vacuum filtration pump is used for solid-liquid separation. The solid product is repeatedly washed with deionized water until the filtrate is colorless (usually 5-7 washes) to remove surface-adsorbed soluble organic matter and residual sodium lignosulfonate. The washed solid product is then dried in a 105℃ oven to constant weight (drying time approximately 12 hours) to obtain hydrothermal carbon loaded with carbon quantum dots, denoted as HC-200-SLS.
[0023] 6. Product characterization and performance testing (1) Scanning electron microscopy analysis The microstructure of hydrothermal carbon was observed using field emission scanning electron microscopy. The results showed that the hydrothermal carbon had a rough surface, abundant pore structure, and exhibited a typical carbon microsphere structure. High-magnification images revealed that the surface of the hydrothermal carbon was uniformly loaded with carbon quantum dots with a particle size of 5-10 nm. These carbon quantum dots were spherical or quasi-spherical, uniformly dispersed without agglomeration. These carbon quantum dots originated from the intramolecular dehydration carbonization of some intermediate products during the hydrothermal carbonization process, and were more easily formed under weakly acidic conditions (pH 4-6) and appropriate heating rates (≥5℃ / min).
[0024] (2) High-resolution transmission electron microscopy analysis The crystal structure of carbon quantum dots was characterized using high-resolution transmission electron microscopy (HRTEM). HRTEM images showed that the carbon quantum dots had an interplanar distance of 0.19 nm, corresponding to the (100) crystal plane of the graphitic carbon ring unit, indicating that the carbon quantum dots have a typical graphitized structure. Selected area electron diffraction (SED) showed diffuse rings, indicating that the carbon quantum dots are a composite structure of amorphous carbon and nanocrystals.
[0025] (3) Fourier transform infrared spectroscopy analysis FTIR analysis of hydrothermal carbon was performed using the KBr pellet method, with a scanning range of 4000-400 cm⁻¹. -1 The results showed that at 3340cm -1 A broad and strong absorption peak appears at 1706 cm⁻¹, attributed to the stretching vibration of hydroxyl groups (-OH), indicating that the surface of hydrothermal carbon is rich in hydroxyl groups; at 1706 cm⁻¹... -1 A moderate absorption peak appears at 1516 cm⁻¹, attributed to the stretching vibration of the carboxyl or carbonyl (C=O) group; at 1516 cm⁻¹... -1 and 1616cm -1 The absorption peak at 1211 cm⁻¹ is attributed to the stretching vibration of the aromatic C=C bond, indicating that the hydrothermal carbon possesses a certain aromatic structure; -1 and 1160cm -1 The absorption peaks appearing at this point are attributed to the stretching vibrations of CO and -COC. The presence of these functional groups endows hydrothermal carbon with good hydrophilicity and heavy metal coordination ability.
[0026] (4) Cd²⁺ adsorption performance test Adsorption test method: A 10 mg / L cadmium nitrate solution was prepared using cadmium nitrate stock solution. The pH of the solution was adjusted to 6.0 ± 0.1 using 0.1 mol / L NaOH and HNO3 solutions. 25 mL of the 10 mg / L cadmium nitrate solution was added to a 50 mL centrifuge tube, along with 25 mg of hydrothermal charcoal (1 g / L). The tube was placed in a constant-temperature water bath shaker at 180 rpm and 25 °C for 24 h. Finally, the solution was filtered through a 0.45 μm needle filter, and the Cd²⁺ concentration was analyzed using a flame atomic absorption spectrophotometer. The adsorption capacity was calculated using the formula: qe = (C₀ - Ce) × V / m.
[0027] Test results: The hydrothermal carbon prepared in this example has an adsorption capacity of 33.21 mg / g for Cd²⁺.
[0028] (5) FTIR comparison analysis before and after adsorption FTIR analysis of the hydrothermal carbon after Cd²⁺ adsorption showed that, compared with the state before adsorption, the carbon density was 3340 cm⁻¹. -1 The decrease in the intensity of the -OH stretching vibration peak at 1706 cm⁻¹ indicates that Cd²⁺ has undergone ion exchange or surface complexation with -OH; -1 The decrease in the intensity of the C=O tensile vibration peak at 1516 cm⁻¹ indicates that Cd²⁺ binds to oxygen-containing functional groups such as C=O through surface complexation; -1 and 1616cm -1 The significant decrease in the stretching vibration peak of the aromatic C=C bond indicates that Cd²⁺ interacts with the π electrons on the benzene ring via a cation-π bond. The synergistic effect of these multiple adsorption mechanisms explains the high adsorption capacity of the hydrothermal carbon in this embodiment.
[0029] Example 2 (Fe-doped hydrothermal carbon for promoting anaerobic fermentation) 1. Raw material pretreatment After drying, corn cobs are pulverized in a high-speed universal pulverizer to below 80 mesh (particle size approximately 180 μm). The pulverized corn cob powder is collected and dried in a 105℃ oven for 12 hours until constant weight is achieved. After cooling, it is placed in a sealed bag and stored in a desiccator for later use. The main components of corn cobs are cellulose (approximately 40%), hemicellulose (approximately 30%), and lignin (approximately 20%), making them a high-quality raw material for hydrothermal carbon.
[0030] 2. Pulp preparation and additive premixing Weigh 10g of the corn cob powder (dry basis) and add it to 100mL of deionized water at a solid-liquid ratio of 1:10. Then add 3wt.% (0.3g) of Span 80 (HLB=4.0) and 3wt.% (0.3g) of Fe(NO3)3·9H2O, stirring until a slurry is formed. Span 80 is a highly lipophilic nonionic surfactant with an HLB value of 4.0. It can form an oil film at the oil-water interface, preventing degraded components from leaving the solid phase and entering the liquid phase, thereby improving the hydrothermal char yield. The addition of Fe(NO3)3·9H2O is 3wt.% (0.3g). The introduction of iron provides essential nutrients for the dark fermentation microorganisms, and Fe is an important component of [Fe-Fe] hydrogenase, which can act as an electron donor in redox reactions.
[0031] Stir the slurry thoroughly for 20 minutes to ensure that Span 80 and iron salts are evenly dispersed in the slurry. The slurry is light brown in color and has a pH of approximately 4.5 (due to the weak acidity caused by the hydrolysis of Fe(NO3)3·9H2O).
[0032] 3. Temperature-programmed reaction The slurry was poured into a sealed reactor, sealed, and a heating program was set: heating to 220°C at a rate of 5°C / min, and maintaining the temperature under autogenous pressure for 5 hours. During the reaction, the pH of the system was controlled at approximately 5.5 by adding 0.5g of acetic acid to the raw material slurry. Acetic acid, as an organic acid, can participate in the hydrothermal carbonization reaction during the reaction without introducing harmful impurities. The autogenous pressure inside the reactor at 220°C was approximately 2.0-2.5MPa.
[0033] 4. Programmed cooling and isothermal treatment After reacting at this temperature for 5 hours, the temperature was lowered to 120°C at a rate of 10°C / min and held at this temperature for 1 hour. This programmed cooling helps Fe³⁺ to fully coordinate with the oxygen-containing functional groups on the surface of carbon quantum dots, forming stable Fe-OC active centers.
[0034] 5. Discharge and Separation After the reaction was completed, the reactor was opened and the material was discharged. Solid-liquid separation was performed using a high-speed centrifuge (8000 r / min, 10 min). The solid product was washed three times alternately with anhydrous ethanol and deionized water to remove unreacted iron salts and organic matter adsorbed on the surface. The washed solid product was then dried in a forced-air drying oven at 80℃ for 12 h to constant weight, yielding Fe-doped hydrothermal carbon microspheres, denoted as Fe-HCM.
[0035] 6. Product characterization and performance testing (1) Scanning electron microscopy and energy dispersive spectroscopy analysis The morphology and elemental distribution of Fe-HCM were characterized using field emission scanning electron microscopy combined with X-ray energy dispersive spectroscopy. SEM images showed that Fe-HCM exhibited a typical carbon microsphere structure with microsphere diameters of approximately 0.5–2 μm and a rough surface. Compared to undoped Fe HCM, the microspheres were smaller and more uniformly dispersed. EDS analysis revealed that the mass fractions of C, O, and Fe in Fe-HCM were 80.8%, 16.5%, and 2.6%, respectively, with atomic fractions of 89.5%, 9.8%, and 0.7%. Surface scan images of Fe showed that Fe was uniformly distributed on the surface of the carbon microspheres without agglomeration, indicating successful Fe loading onto the carbon microsphere surface.
[0036] (2) Transmission electron microscopy analysis TEM images show that the Fe-HCM surface is loaded with a large number of carbon quantum dots with a particle size of approximately 5 nm. The carbon quantum dots are spherical and uniformly dispersed. High-resolution TEM images show that the carbon quantum dots have a crystal interplanar spacing of 0.19 nm, consistent with the carbon quantum dot structure in Example 1. Fe mainly exists in the form of Fe³⁺ on the surface of the carbon quantum dots, forming Fe-OC coordination bonds with oxygen-containing functional groups.
[0037] (3) X-ray photoelectron spectroscopy analysis XPS analysis revealed two characteristic peaks in the Fe 2p spectrum: Fe 2p3 / 2 (710.9 eV) and Fe 2p1 / 2 (724.2 eV), as well as a satellite peak at 719.5 eV, indicating that iron exists in the form of Fe³⁺. The O 1s spectrum showed two peaks at 531.5 eV and 533.0 eV, attributed to Fe-O and CO bonds respectively, confirming the formation of the Fe-OC active center.
[0038] (4) Dark fermentation hydrogen production performance test Preparation of inoculum sludge: 2L of raw anaerobic sludge (from a citric acid wastewater treatment plant) was taken and cultured at 37℃ with 0.4g glucose for 20-25 days to enrich anaerobic microorganisms. The cultured sludge sample was heated in a 90℃ water bath for 30min to inhibit methanogenic bacteria activity and enrich hydrogen-producing bacteria. After heating, it was cooled, and 0.2g glucose was added again and cultured at 37℃ for 2 days to obtain inoculum sludge for dark fermentation. The main characteristic parameters of the inoculum sludge were: pH 7.2±0.1, ammonia nitrogen 560±50mg / L, total organic carbon 2151±113mg / L, chemical oxygen demand 11527±410mg / L, total solids 13.7±0.4wt.%, and volatile solids 60.3±2.1wt.% / TS.
[0039] Fermentation Experiment Method: 5g glucose and 0.15g peptone were added as substrates to a 500mL serum bottle. 600mg / L Fe-HCM (based on the optimal addition amount determined in preliminary experiments) was added, along with 100mL of mesophilic inoculum and 300mL of deionized water. The mixture was thoroughly mixed, and the pH was adjusted to 7.0±0.1 using HCl and NaOH. Nitrogen gas was purged for 3 minutes to remove oxygen from the reactor and maintain an anaerobic environment. All reactors were incubated at 37℃ for 48 hours for anaerobic hydrogen production experiments. Hydrogen production was collected using the water displacement method, and the H2 mixed with CO2 in the gas phase was purified by absorbing the H2S and CO2 mixture in the gas phase with 10% NaOH solution.
[0040] Cumulative hydrogen production data at different time points are shown below. Figure 2 The maximum hydrogen production rate occurred at 15 h, reaching 13.3 mL / (g·h) in the Fe-HCM group.
[0041] (5) Analysis of soluble metabolites High-performance liquid chromatography (HPLC) was used to analyze soluble metabolites (SMPs) during dark fermentation. The SMP and glucose concentrations at different time points in the Fe-HCM group are shown in [Table / Reference]. Figure 3 .
[0042] (6) Microbial community structure analysis High-throughput 16S rRNA sequencing was used to analyze the microbial communities in the control group, HCM group, and Fe-HCM group. The results showed that at the phylum level, Firmicutes was the most prevalent phylum in dark fermentation hydrogen production. After the addition of HCM and Fe-HCM, the abundance of Firmicutes increased from 35% (control group) to 41% (HCM group) and 56% (Fe-HCM group), respectively. At the genus level, Clostridium sensu stricto_1 was the dominant hydrogen-producing bacterium, with its abundance increasing from 25% in the control group to 38% in the HCM group and 51% in the Fe-HCM group, showing a positive correlation with H2 production.
[0043] Example 3 (High-calorific-value hydrothermal char for solid fuels) 1. Raw material pretreatment The medicinal herb residue was provided by Jianghan University Hospital and consisted of a mixture of four different types of medicinal herb residue with a moisture content of 55-60%. After air-drying the residue to approximately 20% moisture content, impurities such as stones, plastic bags, and ropes were manually removed. Longer root and stem residues were chopped. The processed residue was then pulverized using a grinder and passed through an 80-mesh sieve (approximately 180 μm particle size). The sieved sample was collected, mixed thoroughly using a quartering method, and dried in a 105℃ oven for 12 hours until constant weight. After cooling, it was placed in sealed bags and then into desiccants for later use.
[0044] Analysis revealed that the elemental composition of the medicinal herb residue raw material was: C 39.47%, H 6.02%, O 41.95%, N 1.17%. Industrial analysis showed: volatile matter 92.95%, ash 2.16%, fixed carbon 4.89%, and calorific value 15.83 MJ / kg. The raw material was weakly acidic, with a pH of approximately 5.4.
[0045] 2. Pulp preparation and additive premixing Weigh 10g of the above-mentioned Chinese herbal medicine residue powder (dry basis), add 100mL of deionized water at a solid-liquid ratio of 1:10, and add 2wt.% K2CO3 (0.2g) as an activator. No surfactant is added in this embodiment. K2CO3 is a commonly used chemical activator that can react with carbon atoms in hydrothermal carbon during the hydrothermal carbonization process to create pores, while simultaneously promoting dehydration and decarboxylation reactions, thereby increasing the fixed carbon content and calorific value.
[0046] Stir the slurry thoroughly for 10 minutes to ensure that the K2CO3 is evenly dissolved in the water. The slurry is brownish-black with a pH of approximately 11.5 (K2CO3 hydrolyzes to be strongly alkaline).
[0047] 3. Temperature-programmed reaction Pour the slurry into a sealed reactor, seal it, and set the heating program: heat to 280°C at a heating rate of 4°C / min, and maintain the reaction at autogenous pressure for 60 minutes. Do not adjust the pH during the reaction; the natural pH of the system is approximately 7-8. The autogenous pressure inside the reactor at 280°C is approximately 6.0-8.0 MPa.
[0048] 4. Programmed cooling and isothermal treatment After reacting at the temperature for 60 minutes, the temperature was cooled to 120°C at a rate of 10°C / min and held at that temperature for 0.5 hours. Rapid cooling can avoid excessive gasification loss of fixed carbon at high temperatures and maintain the high calorific value of the hydrothermal carbon.
[0049] 5. Discharge and Separation After the reaction is complete, open the reactor and discharge the material. Solid-liquid separation is performed using a Buchner funnel and a vacuum filtration pump. The solid product is repeatedly washed with deionized water until the filtrate is neutral (pH approximately 7, usually 4-5 washes) to remove residual K₂CO₃ and soluble inorganic salts. The washed solid product is then dried in a 105°C oven to constant weight (drying time approximately 8 hours) to obtain hydrothermal carbon, designated HC-280-60.
[0050] 6. Product characterization and performance testing (1) Industrial Analysis Industrial analysis was performed according to GB / T28731-2012. Volatile matter determination: The mass loss rate was measured after heating in a tube furnace at 900±10℃ for 7 min. Ash content determination: The residue was ignited in a muffle furnace at 550±10℃ to constant weight (approximately 3 h) and the mass percentage of the residue was measured. Fixed carbon content was calculated using the differential method: Fixed carbon = 100% - Volatile matter % - Ash %.
[0051] Test results: The hydrothermal carbon prepared in this embodiment has a volatile matter content of 49.5 wt.%, an ash content of 2.0 wt.%, and a fixed carbon content of 48.5 wt.%. Compared with the raw material of Chinese herbal medicine residue (fixed carbon 4.89 wt.%), the fixed carbon content has increased by nearly 10 times, indicating that the dehydration, decarboxylation, and condensation reactions in the hydrothermal carbonization process significantly promote carbon enrichment.
[0052] (2) Elemental analysis The C, H, N and S contents were analyzed using a VarioMacroCube elemental analyzer. The oxygen content was calculated by subtraction: O% = 100% - C% - H% - N% - S% - Ash.
[0053] Test results: C content 70.22%, H content 4.55%, O content 23.53%, N content 1.55%, S content 0.15%. O / C atomic ratio is 0.25, H / C atomic ratio is 0.78. Compared with the raw material of Chinese herbal medicine residue (O / C=0.58, H / C=1.66), O / C and H / C are significantly reduced, indicating that the degree of carbonization and aromatization of hydrothermal carbon is significantly improved, reaching the level of lignite to bituminous coal.
[0054] (3) Calorific value determination The higher heating value (HHV) is calculated using the modified Dulong formula: HHV = 0.3383 × C + 1.422 × (H₂O / 8), where C, H, and O are mass percentages.
[0055] Test results: The hydrothermal char prepared in this embodiment has a calorific value of 29.5 MJ / kg, which is 86% higher than that of the raw material of Chinese herbal medicine residue (15.83 MJ / kg). This calorific value is between that of lignite (15-25 MJ / kg) and bituminous coal (25-35 MJ / kg), and can be used as a high-quality solid fuel.
[0056] (4) Thermogravimetric analysis The combustion characteristics of hydrothermal char were analyzed using thermogravimetric analysis. The TG / DTG characteristic data of hydrothermal char prepared at different reaction temperatures are shown in Table 3-1.
[0057] Table 3-1 Thermogravimetric analysis characteristics of hydrothermal carbon at different reaction temperatures (5) X-ray diffraction analysis XRD analysis showed that the cellulose crystallization peaks near 2θ=15.5°, 22.5° and 34.5° disappeared in the hydrothermal carbon, and only a broad and diffuse diffraction peak appeared near 2θ=23°, corresponding to the (002) crystal plane of graphite carbon. This indicates that cellulose and hemicellulose were completely hydrolyzed during the high-temperature hydrothermal carbonization process, forming an amorphous carbon structure.
[0058] Example 4 (One-step self-activated magnetic hydrothermal carbon for papermaking black liquor) 1. Raw material preparation The black liquor from the sulfate pulping process of a certain paper mill was used directly as raw material. The black liquor is a dark black viscous liquid with a solid content of approximately 10 wt.%, residual alkali (calculated as NaOH) of approximately 8 g / L, and iron content of approximately 0.5 g / L. The black liquor does not require pulverization and can be used directly.
[0059] 2. Pulp preparation and additive premixing Adjust the pH of the black liquor to around 5.5 with acetic acid and stir well.
[0060] 3. Temperature-programmed reaction The pH-adjusted black liquor was pumped into the reactor and heated to 250°C at a rate of 5°C / min. The reaction was maintained at this temperature for 6 hours under autogenous pressure. During the reaction, the pH remained stable at around 5.5.
[0061] 4. Programmed cooling and isothermal treatment The temperature was lowered from 250℃ to 120℃ at a rate of 10℃ / min (taking 13 minutes) and held at that temperature for 1 hour.
[0062] Natural cooling: The samples were allowed to cool naturally from 250°C to room temperature (approximately 25°C) in about 3-4 hours. The FTIR of the programmed cooling samples showed that the C=O peak intensity was significantly higher than that of the naturally cooled samples.
[0063] 5. Discharge and Separation After the reaction is complete, open the reactor and discharge the material. Solid-liquid separation is performed using a Buchner funnel and a vacuum filtration pump. The solid product is repeatedly washed with deionized water until the filtrate is neutral (pH approximately 7, usually 6-8 washes) to remove residual alkali and soluble inorganic salts. The washed solid product is then dried in a 105℃ oven to constant weight (drying time approximately 10 hours) to obtain magnetic hydrothermal carbon.
[0064] 6. Product characterization and performance testing (1) Specific surface area and pore size analysis Specific surface area was determined using the BET method, and pore size distribution was calculated using the BJH method. A certain amount of hydrothermal carbon was degassed at 300℃ for 8 hours, and then N2 adsorption-desorption was measured in a liquid nitrogen environment at 77K.
[0065] Test results: The hydrothermal carbon prepared in this example has a specific surface area of 320 m² / g, a total pore volume of 0.35 cm³ / g, an average pore diameter of 3.8 nm, and a mesoporosity of approximately 65%. This specific surface area is significantly higher than that of ordinary hydrothermal carbon (typically <20 m² / g), demonstrating that the in-situ activation effect of residual alkali in black liquor has a significant pore-forming effect. The N₂ adsorption-desorption isotherm exhibits a typical type IV isotherm and an H₃ hysteresis loop, indicating the presence of a mesoporous structure.
[0066] (2) Magnetic test The hysteresis loop was measured using a vibrating sample magnetometer at room temperature and with an applied magnetic field ranging from -10000 to 10000 Oe.
[0067] Test results: The saturation magnetization (Ms) of the hydrothermal carbon is approximately 5 emu / g, the coercivity (Hc) is close to 0, and the hysteresis loop exhibits an S-shape with no remanence, indicating superparamagnetism. The iron element originally present in the black liquor (approximately 0.5 g / L) is reduced to Fe3O4 magnetic particles during hydrothermal carbonization. The particle size is approximately 10-20 nm, lower than the single-domain critical size of Fe3O4 (approximately 30 nm), thus exhibiting superparamagnetism.
[0068] (3) Magnetic separation effect test Hydrothermal carbon was dispersed in water to form a black suspension (concentration 1 g / L). A permanent magnet (surface magnetic field strength of about 0.3 T) was placed on one side of the container, and the separation effect was observed.
[0069] Test results: After standing for 30 seconds, the hydrothermal carbon was rapidly concentrated on one side of the magnet, and the solution became clear and transparent, indicating that the hydrothermal carbon can be quickly separated and recovered using a magnet. The magnetic separation efficiency can reach over 95%, far exceeding that of conventional centrifugation or filtration methods.
[0070] (4) X-ray diffraction analysis XRD analysis revealed characteristic Fe3O4 diffraction peaks at 2θ = 30.1°, 35.5°, 43.1°, 57.0°, and 62.6°, corresponding to the (220), (311), (400), (511), and (440) crystal planes, respectively. Simultaneously, broad, diffuse peaks resembling those of graphitic carbon appeared near 2θ = 23°. The Fe3O4 grain size was approximately 15 nm (calculated using the Scherrer formula), consistent with the superparamagnetic grain size range.
[0071] (5) Calorific value determination The hydrothermal char obtained in this embodiment has a calorific value of 18.5 MJ / kg, which is lower than 29.5 MJ / kg in Example 3. However, considering that this embodiment uses waste black liquor as raw material and does not require the addition of any chemical reagents, it still has significant economic and environmental benefits from the perspective of resource utilization.
[0072] Key control experiments and demonstration of technical effects To verify the inventiveness and superiority of the process of this invention, a series of control experiments were set up. All experiments used the one-step process described in this invention, and the data were the average of three parallel experiments.
[0073] 1. Experiment on the directional regulation effect of surfactants Using Chinese herbal medicine residue as raw material, the reaction temperature was 240℃, the residence time was 60 min, the solid-liquid ratio was 1:10, and 2wt.% H2SO4 was added as a catalyst. Different surfactants (3wt.% added) were added to investigate the regulatory effect of different surfactants on the product. The results are shown in Table 1.
[0074] Table 1. Effects of different surfactants on the properties of hydrothermal carbon products Results Analysis: Different surfactants can achieve targeted regulation of products: Span 80 (lipophilic, HLB=4.0) can form an oil film at the oil-water interface, preventing degradation components from leaving the solid phase, thus increasing the hydrothermal char yield from 41.47% to 63.51%, an increase of 22.04 percentage points; Tween 80 (hydrophilic, HLB=15.0) can form hydrophilic micelles to promote the transfer of hydrophobic compounds to the liquid phase, thus increasing the bio-oil yield from 7.32% to 10.56%, an increase of 44.3%; Sodium lignosulfonate (anionic, HLB≈8.9) can promote the conversion of high molecular weight PAHs to low molecular weight PAHs, reducing the toxic equivalent of polycyclic aromatic hydrocarbons from 0.2279 mg / kg to 0.0188 mg / kg, a reduction of 91.7%.
[0075] 2. Experiment on the effect of programmed cooling on functional group retention Using reed straw as raw material, the reaction temperature was 200℃, the holding time was 6h, and the pH was 5.5. The effects of different cooling methods on adsorption performance and functional groups were compared. The results are shown in Table 2.
[0076] Table 2. Effects of cooling methods on the performance of hydrothermal carbon Results Analysis: Programmed cooling effectively preserves active oxygen-containing functional groups. During natural cooling, the reaction system takes 2-4 hours to cool from 200℃ to room temperature. This prolonged high-temperature duration leads to the thermal decomposition of oxygen-containing functional groups such as carboxyl and hydroxyl groups (mainly manifested as decarboxylation and dehydration reactions). Programmed cooling (10℃ / min) can lower the temperature to 120℃ within 15-20 minutes, significantly shortening the high-temperature residence time and thus preserving more functional groups. FTIR analysis confirmed that the C=O peak intensity (transmittance 30%) of the programmed-cooled sample was significantly higher than that of the naturally cooled sample (transmittance 50%). The preservation of functional groups is directly reflected in the adsorption performance: the Cd²⁺ adsorption capacity increased from 18.67 mg / g to 33.21 mg / g, an increase of 77.9%. Programmed cooling is one of the key innovative features that distinguishes this invention from conventional hydrothermal carbonization processes.
[0077] 3. Experiment on the effect of pH value on in-situ formation of carbon quantum dots Using corn cobs as raw material, the reaction temperature was 220℃ and the holding time was 5h. The effect of pH on the formation of carbon quantum dots was investigated. The results are shown in Table 3.
[0078] Table 3. Carbon quantum dot formation under different pH conditions Results Analysis: A weakly acidic environment (pH 4-6) is a necessary condition for the in-situ formation of carbon quantum dots. The mechanism may be that under weakly acidic conditions, the intramolecular dehydration carbonization reaction rate of hydrothermal carbonization intermediates (such as furfural, hydroxymethylfurfural, etc.) is moderate, which is conducive to the formation of regular graphitic carbon structures; while under neutral or alkaline conditions, the intermediates tend to transform in other directions (such as rearrangement to form organic acids or polymerization to form macromolecules), which is not conducive to the nucleation and growth of carbon quantum dots. Fluorescence spectroscopy shows that the fluorescence intensity of the products under pH 4-6 conditions (peak 800) is much higher than that at pH 7 (peak 200) and pH 9 (peak <50), and is positively correlated with the amount of carbon quantum dots generated. This experiment proves that by controlling the pH in the range of 4-6, the present invention can simultaneously complete the in-situ formation and loading of carbon quantum dots during hydrothermal carbonization, realizing the "one-pot" preparation of composite materials.
[0079] 4. Experiment on the promoting effect of metal salt modifier (Fe doping) on hydrogen production by dark fermentation Using corn cobs as raw material, the reaction temperature was 220℃, the holding time was 5h, the pH was 5.5, and 3wt.% Span 80 was added. The effects of different metal salt modifiers on hydrogen production by dark fermentation were compared. The results are shown in Table 4.
[0080] Table 4. Effects of different metal salt modifiers on hydrogen production during dark fermentation Results Analysis: Fe doping significantly promoted hydrogen production during dark fermentation. The H2 production of Fe-HCM (3wt.% Fe) was 153.94 mL / g glucose, which was 59.44% higher than the blank group and 28.88% higher than the HCM group (without Fe). The promoting mechanism of Fe included: (1) Fe is an important component of [Fe-Fe] hydrogenase, and the addition of Fe can improve the activity of hydrogenase; (2) Fe³⁺ is reduced to Fe²⁺ in the fermentation system, and the Fe³⁺ / Fe²⁺ redox pair can promote electron transfer; (3) Fe-doped hydrothermal carbon has better conductivity, which can promote direct interspecies electron transfer between hydrogen-producing bacteria. However, excessive Fe doping (8wt.%) had an inhibitory effect, and the H2 production decreased by 7.44% because excessive Fe ions were toxic to microorganisms (the Fe ion content in the liquid phase reached 25.8 mg / L after fermentation). Therefore, the appropriate addition amount of Fe(NO3)3·9H2O is 2-4wt.%.
[0081] 5. Experiment on the effect of reaction temperature on the performance of hydrothermal carbon fuel Using Chinese herbal medicine residue as raw material, with a solid-liquid ratio of 1:10 and a holding time of 60 min, the effects of different reaction temperatures on the performance of hydrothermal carbon fuel were compared. The results are shown in Table 5.
[0082] Table 5. Comparison of fuel performance of hydrothermal char at different reaction temperatures Results Analysis: Reaction temperature is the most critical factor affecting the performance of hydrothermal char fuel. As the temperature increased from 220℃ to 280℃, the fixed carbon content significantly increased from 32.9% to 48.5%, the volatile matter content decreased from 66.2% to 49.5%, and the calorific value increased from 27.93 MJ / kg to 29.5 MJ / kg. This is because high temperature promotes dehydration, decarboxylation, and condensation reactions, leading to the conversion and enrichment of carbon from volatile matter to fixed carbon. When the temperature exceeds 280℃, the fixed carbon content and calorific value tend to stabilize, but the yield decreases (from 35.01% to 28.46%), indicating that 280℃ is the optimal reaction temperature. The programmed heating and cooling strategies of this invention can further optimize fuel performance; the calorific value of the programmed cooling sample (29.5 MJ / kg) is higher than that of the naturally cooled sample (approximately 27.5 MJ / kg).
[0083] The above detailed embodiments fully present four examples and five sets of control experiments of the present invention. Each example includes detailed raw material processing, slurry ratio, process parameters (heating rate, reaction temperature, holding time, cooling rate, isothermal temperature and time), post-treatment steps, and comprehensive product characterization data (SEM, TEM, FTIR, XRD, BET, elemental analysis, industrial analysis, calorific value determination, adsorption performance, fermentation performance, etc.). The control experiments respectively verified the directional regulation effect of surfactants, the effect of programmed cooling on functional group retention, the effect of pH on carbon quantum dot formation, the promoting effect of Fe doping on hydrogen production in dark fermentation, and the effect of reaction temperature on fuel performance.
[0084] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A one-step hydrothermal carbon conversion process, characterized in that: Includes the following steps: S1: Crush solid biomass raw materials to 40-200 mesh, mix with water at a solid-liquid ratio of 1:5-1:20; or use liquid biomass raw materials directly; optionally add 0-5% of the raw material mass of surfactant and / or 0-5% of metal salt modifier, stir evenly to form a slurry; S2: Pump the slurry into a closed reactor and heat it to 180-300°C at a heating rate of 2-10°C / min. Maintain the temperature under autogenous pressure for 1-6 hours. Control the pH of the system to 4-6 during the reaction. S3: After the heat preservation is completed, cool down to 100-150℃ at a rate of 5-15℃ / min and keep at a constant temperature for 0.5-2 hours; S4: After the reaction is complete, the material is discharged, and after solid-liquid separation, washing and drying, a hydrothermal carbon composite material loaded with carbon quantum dots is obtained.
2. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: The metal salt modifier is selected from Fe(NO3)3·9H2O or FeCl3·6H2O, and the amount added is 1-5% of the raw material mass.
3. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: The surfactant is selected from Span 80, Tween 80 or sodium lignosulfonate; wherein the amount of Span 80 added is 2-5%, the amount of Tween 80 added is 1-3%, and the amount of sodium lignosulfonate added is 3-5%.
4. The hydrothermal one-step carbon conversion process as described in claim 3, characterized in that: The surfactant has an HLB value of ≤10 or ≥14.
5. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: The method for controlling the pH value of the system to 4-6 in step two is as follows: add 0.5-3% organic acid by weight of the raw material slurry to the raw material slurry. The organic acid is selected from acetic acid, citric acid or lignin sulfonic acid; or use formic acid, acetic acid or propionic acid generated during the hydrothermal carbonization of biomass as pH adjusters.
6. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: Different combinations of process parameters are selected based on the application scenario of the target product: When used for the remediation of heavy metal pollution: reaction temperature 180-220℃, holding time 4-6 hours, surfactant 3-5% sodium lignosulfonate, no metal salt modifier added or only Ca added. 2+ Salt; When used to promote anaerobic fermentation: reaction temperature 220-260℃, holding time 2-4 hours, metal salt modifier Fe(NO3)3·9H2O 2-4%, surfactant Span 80 2-3%; When used for solid fuels: reaction temperature 260-300℃, holding time 4-6 hours, solid-liquid ratio 1:10~1:15, no surfactant added, add 1-3% K2CO3 or KHCO3.
7. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: When the biomass raw material is papermaking black liquor, the pH of the black liquor is adjusted to 4-6 with acid; the reaction temperature is controlled at 220-280℃, and the holding time is 4-8 hours; metal salt modifiers are optionally added.
8. The hydrothermal one-step carbon conversion process as described in claim 1, characterized in that: The process is a continuous process: the raw material slurry is continuously fed into the reactor at a constant flow rate by a high-pressure slurry pump, while the reacted material is continuously discharged through a back pressure valve; after online solid-liquid separation, the liquid phase is concentrated and reused in step one.
9. A hydrothermal one-step carbon conversion apparatus for any of the processes described in claims 1-8, characterized in that: include: The high-temperature, high-pressure, and corrosion-resistant reactor integrates a multi-stage mixer, heat exchange coils, and a porous material distributor. Multiple temperature sensors, pressure sensors, and online pH sensors are installed inside the reactor, as well as an external heating / cooling circulation system connected to the heat exchange coil. All sensors and the heating / cooling circulation system are connected to a PLC controller. High-pressure slurry pump and high-pressure metering injection pump are connected to the material inlet of the reactor; Back pressure valve installed on the material outlet pipeline of the reactor; An online solid-liquid separator, a washing device, and a drying device are connected sequentially after the material outlet of the reactor; The liquid phase outlet of the online solid-liquid separator is connected to the inlet of the high-pressure slurry pump via a concentration device.